Retinal dysfunction parallels morphologic alterations and precede clinically detectable vascular alterations in Meriones shawi, a model of type 2 diabetes. (November 2018) - Hammoum, Imane; Benlarbi, Maha; Dellaa, Ahmed; Kahloun, Rim; Messaoud, Riadh; Amara, Soumaya; Azaiz, Rached; Charfeddine, Ridha; Dogui, Mohamed; Khairallah, Moncef; Lukáts, Ákos; Ben Chaouacha-Chekir, Rafika
Abstract: Diabetic retinopathy is a major cause of reduced visual acuity and acquired blindness. The aim of this work was to analyze functional and vascular changes in diabetic Meriones shawi ( M.sh ) an animal model of metabolic syndrome and type 2 diabetes. The animals were divided into four groups. Two groups were fed a high fat diet (HFD) for 3 and 7 months, two other groups served as age-matched controls. Retinal function was assessed using full field electroretinogram (Ff-ERG). Retinal thickness and vasculature were examined by optical coherence tomography, eye fundus and fluorescein angiography. Immunohistochemistry was used to examine key proteins of glutamate metabolism and synaptic transmission. Diabetic animals exhibited significantly delayed scotopic and photopic ERG responses and decreases in scotopic and photopic a- and b-wave amplitudes at both time points. Furthermore, a decrease of the amplitude of the flicker response and variable changes in the scotopic and photopic oscillatory potentials was reported. A significant decrease in retinal thickness was observed. No evident change in the visual streak area and no sign of vascular abnormality was present; however, some exudates in the periphery were visible in 7 months diabetic animals. Imunohistochemistry detected a decrease in the expression of glutamate synthetase, vesicular glutamate transporter 1 and synaptophysin proteins. Results indicate that a significant retinal dysfunction was present in the HFD induced diabetes involving both rod and cone pathways and this dysfunction correlate well with the morphological abnormalities reported previously. Furthermore, neurodegeneration and abnormalities in retinal function occur before vascular alterations would be detectable in diabetic M.sh . Highlights: Diabetes induces the alteration of scotopic and photopic pathways. Diabetes induces a decrease in retinal thickness by OCT after 3 and 7 months of diabetes. Apparition of exudates only after 7 months of diabetes. Impairment of glutamate metabolism and synaptic transmission in diabetic Meriones shawi.